ANALISIS PENGARUH PERILAKU PEDAGANG TERHADAP INFLASI - Al-Barra Al-Barra (Program Pascasarjana UIN Sumatera Utara, 2016)
The purpose of this research to determine how big the influence of traders behavior against rising inflation.This research used quantitative research approachusing multiple linear regression analysis techniquesupported by model test and statistical test assistedby Eviews software version 8.The results of research conducted by alpha 5%,the authorconcluded that the results of multiple linear regression analysisshowed simultaneously the variables of overstocking of goods, outstanding issues, scarcity of goods and selling price increases influence against inflation.This research showed thatoverstocking of goods, outstanding issues, scarcity of goods and selling price increasessimultaneouslyaffecting inflation rate in Medan. Overstocking of goods has positive influenceagainst the inflationamounted to 0.039916%. Outstanding issues has positive influenceagainst the rising inflation amounted to6.21594%. Scarcity of goodshas positive influenceagainst the inflationamounted to0.005596%. While selling price increaseshas positive influenceagainst the inflationamounted to0.058903%.